Thermodynamic Study of the Three Fluorobenzamides: Vapor Pressures, Phase Diagrams, and Hydrogen Bonds - Almeida, ARRP (2010)
A static method was used to measure the vapor pressures of crystalline and liquid phases of ortho-, meta-, and para-fluorobenzamides, in the temperature ranges (318.0 to 412.2) K, (336.8 to 432.0) K, and (344.8 to 437.8) K, respectively. The vapor pressures of the crystalline phase of the ortho- and meta-isomers were also measured using the Knudsen effusion method in the pressure ranges (0.1 to 1) Pa. From the experimental results, the standard molar Gibbs energies and enthalpies of sublimation and of vaporization, at T = 298.15 K, and the triple-point results (p, T) for the three compounds were derived. The temperatures and molar enthalpies of fusion were also determined using differential scanning calorimetry and were compared with the values derived from the vapor pressure measurements. The enthalpy of the intermolecular hydrogen bonds N-H center dot center dot center dot O in the studied compounds will be discussed and compared with the values derived for benzamide.